Theory of Planned Behavior Dalam Memprediksi Perilaku Mahasiswa Mendaur Ulang Sampah - Rina Sari Qurniawati; Yulfan Arif Nurohman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2020)
The amount of increasingly uncontrolled waste is an interesting environmental issue among the community. The impact of environmental damage is that there are various disasters in several regions. Increasing the amount of waste that is not followed by improvement of waste management facilities and infrastructure has resulted in the problem of waste becoming complex. The purpose of the study was to find out the attitude of recycling, subjective norms and perceivedbehavioral control influencing recycling behavior. The method of sampling is a non-probability sampling with a purposive sampling technique. Respondents used were 101 respondentswhich is students in Surakarta City. Data analysis was performed using quantitative analysis methods using multiple regression analysis. Based on the testing of the first hypothesis shows that there is no influence between the attitudes of recycling on recycling behavior. While the second hypothesis testing shows that subjective norms influence recycling behavior. Testing the third hypothesis shows that there is a relationship between perceivedbehavioral controlwith recycling behavior.